Interface control of pressure-driven two-fluid flow in microchannels using electroosmosis - Wang, Cheng (2012)
This paper presents an experimental investigation of the pressure-driven two-fluid flow in microchannels with electroosmosis effect. Two fluids, aqueous NaCl solution and aqueous glycerol, were introduced by syringe pumps to flow side by side in a straight microchannel. The external electric field was applied on the NaCl side. Under the same inlet volumetric flowrate condition, the applied electric field was varied. The interface position between the two fluids with the electroosmosis effect was studied in the first part of the experiment using the fluorescence imaging technique. In the second part, the velocity field was measured using the micro-PIV technique. The parameters, flowrate and electric field which affect the interface position and velocity field were investigated. The measured velocity field from the experiment agrees well with that of theoretical analysis.